2012
DOI: 10.1177/1087054712451126
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of ADHD, Substance Use, and Comorbid Problems in Incarcerated Women in Sweden

Abstract: The prevalence rate of ADHD in incarcerated women was high and comparable to that in male offenders. Illicit stimulant use and antisocial personality disorder were significantly more common in women with ADHD. ASRS is useful as a screener in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 45 publications
5
41
2
2
Order By: Relevance
“…In this prison sample, there was a higher prevalence of adult ADHD (17%) compared to estimated prevalence of the disorder found in the general population (2%-3%; [33]). These higher rates support findings of previous studies in prisoners and individuals with substance use disorders (10%-29%; [34,35]). However, consistent with Grieger and Hosser, [28], Gordon et al (2014) [36] failed to find any statistically significant association between ADHD symptoms and convictions or breaches of prison discipline.…”
Section: Attention-deficit/hyperactivity Disorder (Adhd) and Criminalitysupporting
confidence: 90%
“…In this prison sample, there was a higher prevalence of adult ADHD (17%) compared to estimated prevalence of the disorder found in the general population (2%-3%; [33]). These higher rates support findings of previous studies in prisoners and individuals with substance use disorders (10%-29%; [34,35]). However, consistent with Grieger and Hosser, [28], Gordon et al (2014) [36] failed to find any statistically significant association between ADHD symptoms and convictions or breaches of prison discipline.…”
Section: Attention-deficit/hyperactivity Disorder (Adhd) and Criminalitysupporting
confidence: 90%
“…Its validity and reliability are comparable to other standardized structured psychiatric interviews like the Structured Clinical Interview for DSM Disorders. The MINI was previously used in prison populations [22,53,54].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work in this field showed that up to 71% of female prisoners with ADHD are affected by illicit drug dependence prior to incarceration in comparison to 31% of non-ADHD inmates [22].…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto a la PD, se han encontrado prevalencias entre 6 y 43.3% (Baillargeon et al, 2010;Butler et al, 2011;Fazel & Seewald, 2012;Lukasiewicz et al, 2009). Entre los OTP más prevalentes en personas en prisión con TCS, se encuentran los trastornos de personalidad; destacan el trastorno antisocial de la personalidad, los trastornos psicóticos, de ansiedad, del estado de ánimo y por déficit de atención (Butler et al, 2011;Casares-López et al, 2010;Fazel & Baillargeon, 2011;Fazel & Danesh, 2002;Fazel & Seewald, 2012;Fazel & Yu, 2011;Lukasiewicz et al, 2009;Konstenius et al, 2015;Mundt et al, 2013). En la Tabla 2 se presentan algunos estudios observacionales específicos en patología dual en entornos penitenciarios.…”
Section: Mini Entrevista Neuropsiquiátrica Internacional (Mini)unclassified
“…Respecto a las diferencias en las prevalencias, resalta que mientras en reclusos hombres son más frecuentes los trastornos de ansiedad, psicóticos y antisocial de la personalidad, concurrentes con los trastornos por consumo de alcohol y por uso de cannabis, en las mujeres se presentan más los trastornos afectivos, de alimentación, por déficit de atención, de estrés postraumático y límite de la personalidad, concurrentes con el consumo de alcohol y estimulantes (Butler et al, 2011;Konstenius et al, 2015;Martínez-Lanz & Fernández Díaz, 2013;Zlotnick et al, 2008). Sobre diferencias de género en factores de riesgo, se ha visto que en hombres el abuso físico en la infancia predice más la PD, mientras que en las mujeres, el abuso sexual tiene un mayor valor predictivo (Villagrá et al, 2013).…”
Section: Mini Entrevista Neuropsiquiátrica Internacional (Mini)unclassified